2008
DOI: 10.1529/biophysj.107.111377
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High Affinity Fatty Acid Binding Sites on Human Serum Albumin by MM-PBSA Method

Abstract: Human serum albumin (HSA) has seven common fatty acid (FA) binding sites. In this study, we used the molecular mechanics Poisson-Boltzmann surface area method to identify high affinity FA binding sites on HSA in terms of binding free energy. Using multiple HSA-FA (myristate, palmitate) complex models constructed by molecular dynamics simulations, two methods were performed in molecular mechanics Poisson-Boltzmann surface area, the "three-trajectory method" and the "single-trajectory method". The former, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 48 publications
4
64
0
Order By: Relevance
“…It has been also reported that the binding affinity of an FA molecule at the site is much lower than that at the other FA binding sites. 9,17,29) Competitive binding of warfarin and myristate at drug binding site I was therefore not considered in this study.…”
Section: Results and Discussion Warfarin As The Target Drug In This Smentioning
confidence: 99%
See 4 more Smart Citations
“…It has been also reported that the binding affinity of an FA molecule at the site is much lower than that at the other FA binding sites. 9,17,29) Competitive binding of warfarin and myristate at drug binding site I was therefore not considered in this study.…”
Section: Results and Discussion Warfarin As The Target Drug In This Smentioning
confidence: 99%
“…17,29) FA binding sites 5, 4, and 2 are high-affinity sites, and 1 and 3 are low-affinity sites (Fig. 1).…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations